Asuhan Keperawatan pada Ny. M dengan Gangguan Sistem Muskuloskeletal: Post Op Hemiarthoplasty pada Fraktur Collum Femur Dexstra di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Ridho Azi Saputra; Ahmad Zakiudin; Esti Nur Janah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Fractures can lead to disabilities in individuals, which may result from trauma due to accident (Ramadhan & Pristianto, 2022)s. The purpose of this paper is to develop and apply nursing care for Mrs. M, who underwent post-operative hemiarthroplasty for a femoral neck fracture, in the Mawar 2 room at RSUD dr. Soeselo, Tegal Regency. This paper utilizes a descriptive method with a focus on the nursing process approach. The results of the nursing care show that the patient reports pain at the surgical site on the upper right leg, post-operative hemiarthroplasty, with pain described as a pulling sensation in the upper right leg, at a pain scale of 6, and continuous. The client states that she can only lie in bed, with all post-operative activities being assisted by family members. She also reports that she has not received health education on early mobilization and has limited understanding of early immobilization. The nursing diagnoses identified are acute pain, impaired physical mobility, and knowledge deficit. Interventions were based on the SIKI (Nursing Care Standards) and implementation followed the planned interventions. Upon evaluation, one diagnosis—knowledge deficit—was resolved, acute pain was partially resolved, and impaired physical mobility remained unresolved. The results of the nursing care are consistent with the theory. This paper aims to improve skills in providing nursing care.